THE BASIC CAUSES OF INDONESIAN EFL STUDENTS’ ANXIETY IN DOING SPEAKING - Ajeng, Galuh Dwi (Lentera: Jurnal Ilmiah Kependidikan, 2016)
English as foreign language brings a phenomenon in education system. EFL students who do not want to get left behind need to master English to follow the growing of education system. Speaking as one of the basic skills is important to be mastered. Therefore, there are many aspects should be cared for. One of them is students’ speaking anxiety. This research is aimed to find the basic causes of Indonesian EFL students’ speaking Anxiety. The data were gathered from a qualitative research. The sample of this study came from a group of Indonesian students who took Speaking 1 class at STKIP PGRI Bandar Lampung. The research shown that there were four causes of foreign language students’ anxiety: discomfort, fear, shyness, and worry.